Does AI Respect Medical Ethics Principles? A Deep Dive into Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
Does AI Respect Medical Ethics Principles? A Deep Dive into Digital Health The integration of Artificial Intelligence (AI) into healthcare, from diagnos...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care